Self Efficacy and Problem Solving on Drug Addiction Amoung Secondary School Students in Ilorin West - Lasisi, Kamil Adekola; Abdulahi, Suleiman; Abdulkareem, Habibat Bolanle (Indonesian Journal of Educational Science and Technology, 2024)
This study investigated the relationship between self-efficacy, gender, and drug addiction among secondary school students in Ilorin West local government area of Kwara State. A sample of 150 responses was anlysed. Correlation analysis revealed a significant negative association between self-efficacy and drug addiction (r = -0.47, p < 0.05). Additionally, gender displayed a moderate positive correlation with drug addiction (r = 0.52, p < 0.05). However, the regression analysis did not find a significant combined contribution of self-efficacy, drug addiction, and gender to the students' performance (F (2, 147) = 2.87, p > 0.05). The findings suggest that while self-efficacy and gender individually associate with drug addiction, their combined influence does not significantly predict academic performance among secondary school students in Ilorin West.